2019
DOI: 10.1111/maps.13425
|View full text |Cite
|
Sign up to set email alerts
|

Experimental constraints on the solidification of a hydrous lunar magma ocean

Abstract: The identification of hydrogen in a range of lunar samples and the similarity of its abundance and isotopic composition with terrestrial values suggest that water could have been present in the Moon since its formation. To quantify the effect of water on early lunar differentiation, we present new analyses of a high-pressure, high-temperature experimental study designed to model the mineralogical and geochemical evolution of the solidification material equivalent to 700 km deep lunar magma oceans first reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 93 publications
2
16
0
Order By: Relevance
“…They found that olivine is the liquidus phase for all relevant LMO compositions and pressure ranges in the early phase of magma ocean crystallization. Lin et al (2017Lin et al ( , 2020 performed experiments simulating fractional crystallization of a 700 km deep magma ocean (corresponding to crystallization pressures of 0 -3 GPa) with LPUM composition and various water contents, demonstrating that the water content influences the plagioclase/clinopyroxene ratio that crystallizes from the melt, as it has been shown in earlier studies (e.g. Sisson and Grove, 1993).…”
Section: Lmo Solidification Modelssupporting
confidence: 63%
“…They found that olivine is the liquidus phase for all relevant LMO compositions and pressure ranges in the early phase of magma ocean crystallization. Lin et al (2017Lin et al ( , 2020 performed experiments simulating fractional crystallization of a 700 km deep magma ocean (corresponding to crystallization pressures of 0 -3 GPa) with LPUM composition and various water contents, demonstrating that the water content influences the plagioclase/clinopyroxene ratio that crystallizes from the melt, as it has been shown in earlier studies (e.g. Sisson and Grove, 1993).…”
Section: Lmo Solidification Modelssupporting
confidence: 63%
“…Studies of the effect of f O 2 on magma oceans have, to date, been limited to quantifying the link between f O 2 variations and changes in the redox states of the major cation iron ( 13 , 26 , 46 ), or linked directly to models of gas speciation in atmospheres influenced by magma ocean outgassing ( 35 , 36 , 47 ). Variations in solidus and liquidus temperatures of cooling magma oceans have largely been assessed in terms of variations in volatile abundances ( 48 , 49 ). In this study we provide experimental evidence for a direct effect of oxygen fugacity on rock melting properties, in the absence of valence state variations in iron and in the absence of volatiles.…”
Section: High-temperature Experimentsmentioning
confidence: 99%
“…Together with the geophysical techniques discussed in the following section, they form a powerful method to elucidate planetary interiors, even in the case of planets and moons for which we will never be able to obtain direct deep subsurface samples. Lin et al 2020). This experiment illustrates conditions at which the lunar mantle would be partially molten and partially solidified.…”
Section: Compositionmentioning
confidence: 90%
“…Fig.2a Back-scatter electron (BSE) microscope image of a polished section through the run product of a high-pressure experiment mimicking the interior of the Moon (afterLin et al 2020). This experiment illustrates conditions at which the lunar mantle would be partially molten and partially solidified.…”
mentioning
confidence: 99%